Aqueous zinc-manganese battery and preparation method thereof
Patent Information
- Application Number
- CN202611159081.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这些策略均未能有效解决正极侧因电化学反应产物导电性差、逐渐堆积钝化所引发的快速失活问题——该失活机制是导致电池容量衰减和循环寿命缩短的核心瓶颈,而现有手段对其干预能力有限
(1)显著延长循环寿命:通过在锰基正极与隔膜之间设置导电稳定中间层,为导电性差的电化学反应产物提供额外电子传输通道,有效抑制锰基正极钝化失活,显著延长电池的循环寿命。
Smart Images

Figure CN123018173A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aqueous electrochemical energy storage technology, specifically relating to an aqueous zinc-manganese battery and its preparation method. Background Technology
[0002] With the rapid development of renewable energy sources (such as solar and wind power), large-scale energy storage technology has become a key support for solving their intermittency and volatility problems. Among various energy storage technologies, aqueous batteries are considered an important development direction in the field of large-scale energy storage due to their inherent safety, low cost, and environmental friendliness.
[0003] Aqueous zinc-manganese batteries use metallic zinc as the negative electrode, manganese-based materials as the positive electrode, and neutral or weakly acidic aqueous solutions as the electrolyte. They have advantages such as high theoretical capacity (820 mAh / g for zinc negative electrode and about 308 mAh / g for manganese dioxide positive electrode), low redox potential of zinc metal (-0.76 V vs SHE), and abundant resources of positive and negative electrode materials. In recent years, they have received widespread attention from academia and industry.
[0004] However, existing aqueous zinc-manganese batteries still face the following key problems in practical applications: (1) Deactivation of manganese-based cathode: During the charging and discharging process, the manganese-based cathode undergoes a dissolution-deposition reaction. The electrochemical reaction products have poor conductivity and gradually accumulate on the electrode surface to form a passivation layer, which hinders electron transport and ion diffusion. This leads to the deactivation of the manganese-based cathode and a rapid decrease in battery capacity.
[0005] (2) Short cycle life: Due to the above-mentioned deactivation mechanism, traditional aqueous zinc-manganese batteries usually show a significant capacity decrease within a hundred cycles, which is difficult to meet the requirements of large-scale energy storage systems for long cycle life (thousands of cycles or more).
[0006] (3) Poor rate performance: The intrinsic conductivity of manganese-based cathode materials is low, and the insulating properties of electrochemical reaction products lead to a significant decrease in battery performance under high current charge and discharge conditions. Summary of the Invention
[0007] This invention is based on the inventor's discovery and understanding of the following facts and problems: Regarding the aforementioned problems, existing technologies mainly focus on the following directions: first, improving the conductivity of manganese-based cathodes through doping, nanostructure design, or composite conductive carbon materials; second, adding Mn to the electrolyte. 2+ Ions are used to inhibit manganese dissolution or provide reaction ions. However, these strategies have failed to effectively solve the problem of rapid deactivation caused by the poor conductivity of electrochemical reaction products on the positive electrode side and their gradual accumulation and passivation. This deactivation mechanism is the core bottleneck leading to battery capacity decay and shortened cycle life, and existing methods have limited ability to intervene in it.
[0008] Therefore, there is an urgent need to develop a novel battery structure that can directly regulate the deposition behavior of electrochemical reaction products of manganese-based cathodes and improve the interfacial electron / ion transport pathways from a completely new perspective of electrode / electrolyte interface design, so as to achieve high stability and long cycle life.
[0009] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, embodiments of this invention propose an aqueous zinc-manganese battery and a method for its preparation.
[0010] In a first aspect, embodiments of the present invention provide an aqueous zinc-manganese battery, comprising a manganese-based positive electrode, a separator, a zinc negative electrode, and an electrolyte, wherein a conductive and stable intermediate layer is disposed between the manganese-based positive electrode and the separator; the conductive and stable intermediate layer is selected from at least one of carbon felt, carbon cloth, graphite felt, carbon paper, foamed titanium, titanium mesh, and stainless steel mesh.
[0011] The advantages and technical effects of the aqueous zinc-manganese battery of this invention are as follows: (1) Significantly extended cycle life: By setting a conductive and stable intermediate layer between the manganese-based cathode and the separator, an additional electron transport channel is provided for the poorly conductive electrochemical reaction products, which effectively inhibits the passivation and deactivation of the manganese-based cathode and significantly extends the cycle life of the battery.
[0012] (2) Improved rate performance: The three-dimensional porous structure of the conductive and stable intermediate layer provides more reaction interfaces and shorter ion transport paths, so that the battery can still maintain a high specific capacity under high current density.
[0013] (3) Improve coulombic efficiency: By optimizing the reaction interface of manganese-based cathode, side reactions and irreversible capacity loss are reduced, thereby improving the coulombic efficiency of the battery.
[0014] (4) Strong process compatibility: The conductive and stable intermediate layer can be directly used by commercially available products after simple pretreatment, without complicated processing, and is easy to mass-produce.
[0015] (5) Good universality: The battery structure design of the present invention can be adapted to different types of manganese-based cathode materials and various electrolyte systems.
[0016] Optionally, the conductive and stable intermediate layer is a carbon felt and / or carbon cloth.
[0017] Optionally, the conductive and stable intermediate layer is a hydrophilized carbon felt and / or carbon cloth.
[0018] Optionally, the hydrophilization treatment includes at least one of concentrated nitric acid treatment, plasma treatment, hydrogen peroxide treatment, ammonia treatment, ozone treatment, and corona treatment.
[0019] Optionally, the concentrated nitric acid treatment involves placing the conductive and stable intermediate layer in concentrated nitric acid at 60-100°C for 1-3 hours.
[0020] Optionally, the thickness of the conductive stabilizing intermediate layer is 0.01~6 mm, the porosity is ≥60%, and the sheet resistance is ≤50 Ω / cm².
[0021] Optionally, the manganese-based positive electrode includes a positive electrode current collector and a positive electrode active layer coated on the surface of the positive electrode current collector. The positive electrode active layer includes a positive electrode active material, a conductive agent, and a binder. Alternatively, the manganese-based positive electrode includes a positive electrode current collector and a positive electrode active material electrodeposited or hydrothermally grown on the positive electrode current collector. The positive electrode active material is at least one selected from MnO2, Mn2O3, Mn3O4, MnO, MnCO3, ZnO, basic zinc sulfate, MgO, and CaO.
[0022] Optionally, the diaphragm is a glass fiber diaphragm, a non-woven fabric diaphragm, a polyethylene diaphragm, or a polypropylene diaphragm.
[0023] Optionally, the zinc negative electrode is a zinc foil, a zinc powder composite electrode, and an electrodeposited zinc electrode; wherein, the zinc powder composite electrode comprises a negative current collector and a negative active layer coated on the surface of the negative current collector, the negative active layer comprising zinc powder, a conductive agent, and a binder; the electrodeposited zinc electrode comprises a negative current collector and a zinc layer electrodeposited on the surface of the negative current collector.
[0024] Optionally, the electrolyte contains Zn. 2+ and Mn 2+ An aqueous solution containing Zn 2+ Concentrations range from 0.5 to 3 mol / L, Mn 2+ The concentration is 0.2~1 mol / L.
[0025] Optionally, the electrolyte may further contain organic additives, such as sodium dodecyl sulfate and / or polyethylene glycol.
[0026] Secondly, embodiments of the present invention provide a method for preparing an aqueous zinc-manganese battery, comprising the following steps: Preparation of manganese-based cathodes; The conductive and stable intermediate layer is cut to the same size as the manganese-based positive electrode; Prepare the zinc negative electrode; Prepare the electrolyte; The aqueous zinc-manganese battery described in the first aspect is obtained by stacking manganese-based positive electrode, conductive and stable intermediate layer, separator, and zinc negative electrode in that order, injecting electrolyte, and then encapsulating.
[0027] The advantages and technical effects of the preparation method of this invention are as follows: 1. The process is simple and easy to operate, requiring no complex equipment. It is highly compatible with existing aqueous zinc-manganese battery manufacturing processes and is easy to scale up for production. 2. The conductive and stable intermediate layer can be directly made from commercially available products, which only need to be cut and used without significantly increasing the battery manufacturing cost. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the structure of an aqueous zinc-manganese battery according to an embodiment of the present invention.
[0029] Figure 2 This is a schematic diagram of the traditional aqueous zinc-manganese battery structure for Comparative Example 1.
[0030] Figure 3 The characteristic charge-discharge curves of the aqueous zinc-manganese battery in Example 1 are shown.
[0031] Figure 4 This is a comparison chart of the cycle performance of the aqueous zinc-manganese battery of Example 1 and the conventional aqueous zinc-manganese battery of Comparative Example 1.
[0032] Figure 5 This is a comparison chart of the rate performance of the aqueous zinc-manganese battery in Example 1 and the conventional aqueous zinc-manganese battery in Comparative Example 1.
[0033] Figure 6 The graph shows the long-cycle performance of the aqueous zinc-manganese battery in Example 1.
[0034] Figure 7 This is a comparison of the electrochemical impedance spectroscopy (EIS) of the aqueous zinc-manganese battery of Example 1 and the conventional aqueous zinc-manganese battery of Comparative Example 1.
[0035] Figure 8 This is a comparison chart of electrolyte adsorption amounts between the aqueous zinc-manganese battery of Example 1 and the conventional aqueous zinc-manganese battery of Comparative Example 1.
[0036] Figure 9 The image shows a micron-scale CT image (left) and a pixel intensity projection image (right) of the conductive and stable intermediate layer of the aqueous zinc-manganese battery in Example 1 after 100 cycles.
[0037] Explanation of reference numerals in the attached diagram: 1-Manganese-based positive electrode; 2-Separator; 3-Zinc negative electrode; 4-Conductive stabilizing intermediate layer. Detailed Implementation
[0038] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0039] In a first aspect, embodiments of the present invention provide an aqueous zinc-manganese battery, such as... Figure 1As shown, the aqueous zinc-manganese battery includes a manganese-based positive electrode 1, a separator 2, a zinc negative electrode 3, and an electrolyte, and a conductive stabilizing intermediate layer 4 is provided between the manganese-based positive electrode 1 and the separator 2; the conductive stabilizing intermediate layer 4 is a carbon material (such as carbon felt, carbon cloth, graphite felt, carbon paper), a metal material (foamed titanium, inert metal mesh (titanium mesh and stainless steel mesh)) or a conductive composite material formed by carbon material and metal material.
[0040] and Figure 2 Unlike the conventional aqueous zinc-manganese battery shown, in the aqueous zinc-manganese battery of this invention, a conductive stabilizing intermediate layer is provided between the manganese-based positive electrode and the separator. Specifically, the manganese-based positive electrode includes a positive electrode current collector and a positive electrode active layer disposed on the surface of the positive electrode current collector. That is to say, the conductive stabilizing intermediate layer is an independent self-supporting layer that is physically in contact with both the positive electrode active layer and the separator but is separated from them, forming a sandwich structure of "positive electrode active layer - conductive stabilizing intermediate layer - separator" with the positive electrode active layer and the separator.
[0041] The conductive and stable intermediate layer is conductive and chemically stable, as detailed below: 1. Electrochemical inertness: within the applied voltage window (e.g., 0.8~1.85 V vs. Zn / Zn²). + The conductive and stable intermediate layer itself does not undergo oxidation or reduction reactions, does not contribute to capacity, and obviously does not produce side reaction gases.
[0042] 2. Resistant to acid corrosion: The conductive and stable intermediate layer contains Mn²⁺. + / Zn² + It does not undergo chemical dissolution or structural collapse when immersed in a weakly acidic electrolyte for a long time.
[0043] 3. Does not undergo irreversible reactions with electrochemical reaction products: The conductive and stable intermediate layer does not react with the adsorbed Mn²⁺. + Alternatively, the electrochemical reaction products deposited on the surface of the manganese-based cathode may undergo bonding reactions, and the electrode may function solely through physical adsorption and conductivity.
[0044] 4. Long-term structural stability: The conductive and stable intermediate layer maintains its pore structure and conductivity without decay under repeated expansion / contraction stress cycles of hundreds to thousands.
[0045] During charging and discharging, the conductive and stable intermediate layer mainly functions through the following physical mechanisms: 1. Enhanced conductivity: The three-dimensional conductive network of the conductive and stable intermediate layer is in close contact with the manganese-based cathode, providing additional electron transport channels for electrochemical reaction products (such as ZnMn2O4) deposited on the surface of the manganese-based cathode, avoiding the "electron island" effect caused by the accumulation of poorly conductive electrochemical reaction products to form a passivation layer.
[0046] 2. Adsorption stability: The conductive and stable intermediate layer has a large specific surface area, providing abundant adsorption sites for active substances and increasing the effective contact area between the electrolyte and the manganese-based cathode, thus effectively adsorbing Mn from the electrolyte. 2+ Ions, and promote Mn 2+ Ions are uniformly deposited on the surface of the manganese-based cathode, inhibiting the formation of irreversible products and stabilizing the manganese-based cathode.
[0047] 3. Electrolyte storage: The conductive and stable intermediate layer has high porosity and can store additional electrolyte, ensuring that the manganese-based cathode reaction interface is always fully wetted and slowing down the performance degradation caused by electrolyte depletion.
[0048] 4. Optimize interfacial reaction kinetics: The three-dimensional porous structure of the conductive and stable intermediate layer provides more reaction interfaces, accelerating ion transport and charge transfer.
[0049] 5. Buffering effect: Some conductive and stable intermediate layers (such as carbon felt, carbon cloth, graphite felt) have a flexible three-dimensional structure, which can buffer the volume expansion / contraction of manganese-based cathode materials during cycling and maintain the integrity of the manganese-based cathode structure.
[0050] Through the aforementioned physical mechanism, the aqueous zinc-manganese battery of this invention achieves a significant improvement in cycle stability and rate performance without drastically altering the existing battery manufacturing process.
[0051] Optionally, the conductive and stabilizing intermediate layer is carbon felt and / or carbon cloth. Carbon felt and carbon cloth have a three-dimensional conductive network structure, high porosity, and good chemical stability, which can tightly adhere to the manganese-based cathode, providing sufficient electron transport channels and attachment sites for electrochemical reaction products.
[0052] Optionally, the conductive and stable intermediate layer is a hydrophilized carbon felt and / or carbon cloth. The hydrophilization treatment increases the oxygen-containing functional groups on the surface of the carbon felt / carbon cloth, improving its wettability to the electrolyte and its resistance to Mn²⁺. + Adsorption capacity.
[0053] Optionally, the hydrophilization treatment includes at least one of concentrated nitric acid treatment, plasma treatment, hydrogen peroxide treatment, ammonia treatment, ozone treatment, and corona treatment.
[0054] Optionally, the concentrated nitric acid treatment involves placing the conductive and stable intermediate layer in concentrated nitric acid at 60~100℃ (e.g., 60℃, 70℃, 80℃, 90℃, 100℃, etc.) for 1~3 hours (e.g., 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc.).
[0055] Optionally, the thickness of the conductive stabilizing intermediate layer is 0.01~6 mm, for example 0.01 mm, 0.1 mm, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, etc., with a porosity ≥60%, for example 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc., and a sheet resistivity ≤50 Ω / cm², for example 50 Ω / cm², 40 Ω / cm², 30 Ω / cm², 20 Ω / cm², 10 Ω / cm², 8 Ω / cm², 6 Ω / cm², 4 Ω / cm², 2 Ω / cm², 1 Ω / cm², etc. A conductive stabilizing intermediate layer that meets the aforementioned conditions possesses sufficient mechanical strength and electronic conductivity, while also providing ample porosity for electrolyte retention and active substance adsorption.
[0056] Optionally, the positive current collector is titanium foil, stainless steel foil, graphite foil, or carbon cloth.
[0057] Optionally, the manganese-based positive electrode includes a positive electrode current collector (such as carbon cloth, titanium foil, titanium mesh, or stainless steel foil) and a positive electrode active layer coated on the surface of the positive electrode current collector. The positive electrode active layer includes a positive electrode active material, a conductive agent, and a binder. Alternatively, the manganese-based positive electrode includes a positive electrode current collector (such as carbon cloth, titanium foil, titanium mesh, or stainless steel foil) and a positive electrode active material electrodeposited or hydrothermally grown on the positive electrode current collector. The positive electrode active material can be at least one of directly manganese-containing oxides, such as MnO2, Mn2O3, Mn3O4, MnO, MnCO3, and ZnO, or at least one of indirect manganese-containing oxides, such as basic zinc sulfate (ZSH), MgO, and CaO.
[0058] Optionally, the separator is a glass fiber separator, non-woven fabric, hydrophilic polyethylene / polypropylene separator, or other aqueous battery separator. Optionally, the thickness of the separator is 0.2~3 mm.
[0059] Optionally, the zinc negative electrode is a zinc foil, a zinc powder composite electrode, and an electrodeposited zinc electrode; wherein, the zinc powder composite electrode comprises a negative electrode current collector (copper foil, stainless steel foil, or carbon cloth) and a negative electrode active layer coated on the surface of the negative electrode current collector, the negative electrode active layer comprising zinc powder, a conductive agent, and a binder; the electrodeposited zinc electrode comprises a negative electrode current collector (such as copper foil, stainless steel foil, or carbon cloth) and a zinc layer electrodeposited on the surface of the negative electrode current collector. Optionally, the thickness of the zinc negative electrode is 10~200 μm.
[0060] Optionally, the electrolyte contains Zn. 2+ and Mn 2+ An aqueous solution containing Zn 2+ Concentrations range from 0.5 to 3 mol / L, Mn 2+The concentration is 0.2~1 mol / L.
[0061] Optionally, the electrolyte may further contain organic additives, such as sodium dodecyl sulfate and / or polyethylene glycol.
[0062] Secondly, embodiments of the present invention provide a method for preparing an aqueous zinc-manganese battery, comprising the following steps: Preparation of manganese-based cathodes; The conductive and stable intermediate layer is cut to the same size as the manganese-based positive electrode; Prepare the zinc negative electrode; Prepare the electrolyte; The aqueous zinc-manganese battery described in the first aspect is obtained by stacking manganese-based positive electrode, conductive and stable intermediate layer, separator, and zinc negative electrode in that order, injecting electrolyte, and then encapsulating.
[0063] The preparation method of this invention is simple and convenient to operate, requires no complex equipment, is highly compatible with existing aqueous zinc-manganese battery preparation processes, and is easy to scale up for production. In addition, the conductive and stable intermediate layer can be directly used as a commercially available product, which only needs to be cut and used, without significantly increasing the battery manufacturing cost.
[0064] The present invention will now be described in detail with reference to the embodiments and accompanying drawings.
[0065] Example 1 (Optimal Solution) This embodiment provides a specific preparation method for a highly stable, long-cycle aqueous zinc-manganese battery. Step 1: Preparation of manganese-based cathode Weigh 7 g ZSH, 2 g Super P conductive carbon black, and 1 g PVDF, add NMP solvent, and grind in an agate mortar for 20 minutes until a uniform slurry is formed. Coat the slurry evenly onto a 0.1 mm thick titanium foil surface, with a coating density of approximately 6 mg / cm². Dry in a 60℃ vacuum oven for 12 hours, then cut into 12 mm diameter discs for later use.
[0066] Step 2: Pretreatment of the conductive and stable intermediate layer A 1 mm thick carbon felt (domestic, polyacrylonitrile (PAN) based, with a bulk density of 0.15 g / cm³) was selected. 3 Porosity 85%, surface resistivity 10 Ω / cm², specific surface area 120 m² 2 / g), cut into round pieces with a diameter of 12 mm.
[0067] Step 3: Zinc Anode Preparation Commercial zinc foil (50 μm thick, 99.99% pure) was cut into 12 mm diameter discs and ultrasonically cleaned for 10 minutes each with acetone, anhydrous ethanol, and deionized water, and then dried for later use.
[0068] Step 4: Electrolyte preparation Weigh 57.51 g of ZnSO4·7H2O (molecular weight 287.56) and 8.45 g of MnSO4·H2O (molecular weight 169.02), dissolve them in deionized water, and bring the volume to 100 mL to obtain a 2 mol / L ZnSO4 + 0.5 mol / L MnSO4 electrolyte. Stir at room temperature until completely dissolved.
[0069] Step 5: Assemble the aqueous zinc-manganese battery Assemble the CR2032 coin cell in the following order: positive electrode shell → titanium foil / positive electrode layer (top) → carbon felt → glass fiber separator (1 mm thick, 16 mm diameter) → zinc negative electrode → stainless steel gasket → spring sheet → negative electrode shell. Inject approximately 250 μL of electrolyte, ensuring complete wetting of the separator and carbon felt. Seal tightly using a sealing machine.
[0070] Example 2 (Alternative Solution for Positive Electrode Active Material) The ZSH in Example 1 was replaced directly with MnO2 in the same mass ratio. 7 g of MnO2 (commercial α-MnO2, 99% purity), 2 g of Super P conductive carbon black, and 1 g of PVDF (molecular weight 1 million) were weighed and ground in an agate mortar for 20 minutes. An appropriate amount of NMP solvent was added, and the mixture was ground until a uniform slurry was formed. The slurry was then uniformly coated onto the surface of a 0.1 mm thick titanium foil, with a coating density of approximately 5 mg / cm². The foil was dried in a vacuum drying oven at 60°C for 12 hours, and then cut into 12 mm diameter discs for later use. All other conditions were exactly the same as in Example 1.
[0071] Example 3 (Carbon Cloth Alternative) The carbon felt (1 mm thick) in Example 1 was replaced with carbon cloth (0.5 mm thick, 60% porosity, 10 Ω / cm² resistivity, 120 m² specific surface area). 2 / g), and the carbon cloth was hydrophilized (treated with 68% concentrated nitric acid at 80°C for 2 hours). Other conditions were exactly the same as in Example 1.
[0072] Example 4 (Alternative to titanium foam) The carbon felt in Example 1 was replaced with titanium foam (1.5 mm thick, 75% porosity, and approximately 500 g / m² areal density). Before use, the titanium foam was ultrasonically cleaned sequentially with acetone, ethanol, and deionized water; no additional hydrophilication treatment was required. Other conditions remained the same as in Example 1.
[0073] Example 5 (Different Electrolyte Schemes) The electrolyte was changed to: 1.5 mol / L ZnSO4 + 0.3 mol / L MnSO4 + 0.05 mol / L sodium dodecyl sulfate (Pym), and other conditions were the same as in Example 1.
[0074] Example 6 (Zinc Powder Composite Electrode) The zinc anode was replaced with a zinc powder composite electrode: zinc powder:Super P:PVDF = 8:1:1 (mass ratio), mixed and ground into a slurry using NMP as a solvent, and coated onto a 20 μm thick carbon cloth, with a coating surface density of approximately 8 mg / cm² (corresponding to a zinc loading of approximately 6.4 mg / cm²). It was then vacuum dried at 60°C for 12 hours. Other conditions were the same as in Example 1.
[0075] Comparative Example 1 (without a conductive stable intermediate layer) Aqueous zinc-manganese batteries were prepared according to the method of Example 1, except that carbon felt was not used. All other conditions were exactly the same as in Example 1.
[0076] Performance testing 1. Electrochemical performance testing After the batteries assembled in Example 1 and Comparative Example 1 were left to stand for 4 hours, charge-discharge cycle tests were conducted at room temperature and a current density of 0.2 A / g, with a voltage window of 0.8–1.85 V. The test results are shown below. Figures 3-6 The aqueous zinc-manganese battery of Example 1 exhibited a stable specific capacity of approximately 150 mAh / g (based on the mass of the positive electrode active material) during the first 5 cycles, and maintained a capacity retention of >98.5% after 1400 cycles, with an average coulombic efficiency of >98%. In contrast, the conventional aqueous zinc-manganese battery of Comparative Example 1 exhibited a capacity retention of less than 40% after 100 cycles, significantly inferior to the >98.5% capacity retention of Example 1 after 1400 cycles.
[0077] Figure 3 shows the characteristic charge-discharge curves of the aqueous zinc-manganese battery of Example 1. The curves exhibit typical plateau characteristics of alkaline zinc-manganese batteries, and the polarization shows no significant increase after 1000 cycles. Figure 4 compares the cycle performance of the aqueous zinc-manganese battery of Example 1 with that of the conventional aqueous zinc-manganese battery of Comparative Example 1. It can be seen that the capacity retention of the aqueous zinc-manganese battery of Example 1 is much better than that of Comparative Example 1 after 100 cycles. Figure 5 compares the rate performance of the aqueous zinc-manganese battery of Example 1 with that of the conventional aqueous zinc-manganese battery of Comparative Example 1. It can be seen that the aqueous zinc-manganese battery of Example 1 maintains a higher specific capacity than that of Comparative Example 1 at rates of 1 A / g, 2 A / g, and 3 A / g, and the average coulombic efficiency is >98%. Figure 6 The graph shows the long-cycle performance of the aqueous zinc-manganese battery of Example 1, demonstrating the long-cycle stability of the aqueous zinc-manganese battery of Example 1 under optimized conditions, wherein the capacity retention rate is >98.5% after 1400 cycles.
[0078] The stable specific capacity, capacity retention rate after 1400 cycles, and coulombic efficiency of the aqueous zinc-manganese batteries in Examples 2-6 are similar to those in Example 1.
[0079] 2. Electrochemical Impedance Spectroscopy (EIS) Test At room temperature, the aqueous zinc-manganese battery of Example 1 and the conventional aqueous zinc-manganese battery of Comparative Example 1 were charged to 1.8V and their AC impedance spectra were measured. The test results are as follows: Figure 7 As shown, the charge transfer resistance of the aqueous zinc-manganese battery in Example 1 is significantly lower than that of the conventional aqueous zinc-manganese battery in Comparative Example 1, indicating that the introduction of the conductive and stable intermediate layer effectively improves the electronic conductivity and ion transport capability of the manganese-based positive electrode side.
[0080] 3. Electrolyte Adsorption Capacity Test At room temperature, the electrolyte adsorption capacity of the aqueous zinc-manganese battery of Example 1 and the conventional aqueous zinc-manganese battery of Comparative Example 1 were tested respectively. The test results are as follows. Figure 8 As shown, the electrolyte adsorption amount in Example 1 is significantly higher than that in Comparative Example 1, indicating that the three-dimensional porous structure of the conductive and stable intermediate layer can store additional electrolyte, ensuring that the manganese-based cathode reaction interface is always fully wetted.
[0081] 4. Structural stability test of the conductive and stable intermediate layer After cycling the aqueous zinc-manganese battery of Example 1 100 times at a current density of 0.2 A / g, the battery was disassembled, the conductive and stable intermediate layer was removed, and micro-computed tomography (micro-CT) was performed. The test results are as follows: Figure 9 As shown, the conductive and stable intermediate layer maintains a complete three-dimensional porous structure without obvious collapse or damage, and its pixel intensity projection map shows that the electrochemical reactants are evenly distributed inside the conductive and stable intermediate layer, proving that the conductive and stable intermediate layer has good structural stability and material adsorption capacity.
[0082] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0083] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. An aqueous zinc-manganese battery, characterized in that, It includes a manganese-based positive electrode, a separator, a zinc negative electrode, and an electrolyte, and a conductive stabilizing intermediate layer is provided between the manganese-based positive electrode and the separator; the conductive stabilizing intermediate layer is selected from at least one of carbon felt, carbon cloth, graphite felt, carbon paper, foamed titanium, titanium mesh, and stainless steel mesh.
2. The aqueous zinc-manganese battery according to claim 1, characterized in that, The conductive and stable intermediate layer is carbon felt and / or carbon cloth.
3. The aqueous zinc-manganese battery according to claim 1, characterized in that, The conductive and stable intermediate layer is a hydrophilized carbon felt and / or carbon cloth.
4. The aqueous zinc-manganese battery according to claim 3, characterized in that, The hydrophilization treatment includes at least one of concentrated nitric acid treatment, plasma treatment, hydrogen peroxide treatment, ammonia treatment, ozone treatment, and corona treatment; Optionally, the concentrated nitric acid treatment involves placing the conductive and stable intermediate layer in concentrated nitric acid at 60-100°C for 1-3 hours.
5. The aqueous zinc-manganese battery according to claim 1, characterized in that, The thickness of the conductive and stable intermediate layer is 0.01~6 mm, the porosity is ≥60%, and the sheet resistance is ≤50 Ω / cm².
6. The aqueous zinc-manganese battery according to claim 1, characterized in that, The manganese-based positive electrode includes a positive electrode current collector and a positive electrode active layer coated on the surface of the positive electrode current collector. The positive electrode active layer includes a positive electrode active material, a conductive agent, and a binder. Alternatively, the manganese-based positive electrode includes a conductive substrate and a positive electrode active material electrodeposited or hydrothermally grown on the conductive substrate. The positive electrode active material is at least one of MnO2, Mn2O3, Mn3O4, MnO, MnCO3, ZnO, basic zinc sulfate, MgO, and CaO.
7. The aqueous zinc-manganese battery according to claim 1, characterized in that, The diaphragm is a glass fiber diaphragm, non-woven fabric, polyethylene diaphragm, or polypropylene diaphragm.
8. The aqueous zinc-manganese battery according to claim 1, characterized in that, The zinc negative electrode comprises zinc foil, zinc powder composite electrode, and electrodeposited zinc electrode; wherein, the zinc powder composite electrode includes a negative current collector and a negative active layer coated on the surface of the negative current collector, the negative active layer comprising zinc powder, a conductive agent, and a binder; the electrodeposited zinc electrode includes a conductive substrate and a zinc layer electrodeposited on the surface of the conductive substrate.
9. The aqueous zinc-manganese battery according to claim 1, characterized in that, The electrolyte is an aqueous solution containing Zn 2+ and Mn 2+ , wherein the concentration of Zn 2+ is 0.5-3 mol / L and the concentration of Mn 2+ is 0.2-1 mol / L. Optionally, the electrolyte may further contain organic additives, such as sodium dodecyl sulfate and / or polyethylene glycol.
10. The method for preparing an aqueous zinc-manganese battery according to any one of claims 1 to 9, characterized in that, Includes the following steps: Preparation of manganese-based cathodes; The conductive and stable intermediate layer is cut to the same size as the manganese-based positive electrode; Prepare the zinc negative electrode; Prepare the electrolyte; The aqueous zinc-manganese battery is obtained by stacking manganese-based positive electrode, conductive and stable intermediate layer, separator, and zinc negative electrode in that order, injecting electrolyte, and then encapsulating.
